IMPLEMENTASI APLIKASI GORESTAN UNTUK PENGURANGAN FOOD WASTE DI RESTAURANT DAN TOKO MAKANAN - Nurul Faujiah; Muhammad Renaga Shafar Anggara; Lukman Abdul Azizul Hakim (CV. Denasya Smart Publisher, 2026)
This Integration Project II discusses the implementation of the Gorestan application as a solution to reduce food waste in restorans and food stores. Gorestan is a digital platform that facilitates the sale of surplus food that is still suitable for consumption at discounted prices. The application also offers a “mystery food” feature that provides an engaging experience for consumers. This study emphasizes the importance of reducing food waste as an effort for sustainability and business efficiency. The implementation of Gorestan is expected to help business partners manage food stock, enhance their image as environmentally conscious businesses, and provide innovative solutions to food waste challenges.